A Preliminary Investigation of the Air-Bone Gap: Changes in Intracochlear Sound Pressure With Air- and Bone-conducted Stimuli After Cochlear Implantation. Issue 9 (October 2016) - Banakis Hartl, Renee M.; Mattingly, Jameson K.; Greene, Nathaniel T.; Jenkins, Herman A.; Cass, Stephen P.; Tollin, Daniel J.
Abstract : Hypothesis: A cochlear implant electrode within the cochlea contributes to the air-bone gap (ABG) component of postoperative changes in residual hearing after electrode insertion. Background: Preservation of residual hearing after cochlear implantation has gained importance as simultaneous electric-acoustic stimulation allows for improved speech outcomes. Postoperative loss of residual hearing has previously been attributed to sensorineural changes; however, presence of increased postoperative ABG remains unexplained and could result in part from altered cochlear mechanics. Here, we sought to investigate changes to these mechanics via intracochlear pressure measurements before and after electrode implantation to quantify the contribution to postoperative ABG. Methods: Human cadaveric heads were implanted with titanium fixtures for bone conduction transducers. Velocities of stapes capitulum and cochlear promontory between the two windows were measured using single-axis laser Doppler vibrometry and fiber-optic sensors measured intracochlear pressures in scala vestibuli and tympani for air- and bone-conducted stimuli before and after cochlear implant electrode insertion through the round window. Results: Intracochlear pressures revealed only slightly reduced responses to air-conducted stimuli consistent with previous literature. No significant changes were noted to bone-conducted stimuli after implantation. Velocities of the stapes capitulum and the cochlear promontory to both stimuli were stable after electrode placement. Conclusion: Presence of a cochlear implant electrode causes alterations in intracochlear sound pressure levels to air, but not bone, conducted stimuli and helps to explain changes in residual hearing noted clinically. These results suggest the possibility of a cochlear conductive component to postoperative changes in hearing sensitivity.